Case study: Effectiveness of problem based learning in mathematics learning - Anugrah, Sherlynggar; Mubarok, Wildan Khusni (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2024)
This study aims to determine the effectiveness of Problem Based Learning (PBL) to improve mathematics learning outcomes. This research uses a literature study approach with reference data including a number of previous studies that are combined and analyzed for generalization. This research uses content data analysis techniques on a number of valid information based on context. context. The results of the combination and analysis that have been carried out will be generalized. This research contains educational problems, especially in mathematics learning due to Covid-19, the nature of education, the definition of mathematics learning and the form of Problem Based Learning (PBL), as well as research evidence regarding the effectiveness of the application of Problem Based Learning (PBL) in mathematics learning. The results obtained are that the Problem Based Learning (PBL) model is proven to be more effective in improving student learning outcomes in mathematics learning. By utilizing the Problem Based Learning (PBL) method, students can improve their learning outcomes. Students will be faster in understanding the material. In addition, with Problem Based Learning (PBL) students are also trained to always think critically in solving problems in everyday life.